An Empirical Analysis on The Influence of Agricultural Research and Development on Agricultural Output in Sub-Saharan Africa: An Endogenous Growth and Public Choice Theory Approach - Songose, Bismark Ibrahim (Université d'Ottawa | University of Ottawa, 2022)
Since independence, many sub-Saharan African (SSA) countries have strived to find permanent solutions to persistent patterns of sluggish economic growth and endemic poverty. For some of these economies, the solution to the problem demands the use of fiscal policy to build up quality and durable critical infrastructures, such as public health facilities, educational facilities, transportation networks, reliable energy supply and many others. According to countries like Ghana and Nigeria, the rationale for this growth strategy is the idea that building and utilizing these critical infrastructures create new employment opportunities and enhance economic productivity. For other economies, including Senegal and the Gambia, amplifying the role of monetary policy to bolster economic activity by controlling interest rates and inflation is seen as an equally important alternative growth strategy, and as a complement to the fiscal policy approach. Despite modest economic improvements after more than five decades, these challenges persist – economic growth continues to be sluggish, poverty rate has consistently failed to fall below the global average, infant mortality rate has not seen significant improvement, quality critical public infrastructures remain lacking, and most of the economies continue to be characterized by inefficiency. With the intention of exploring other growth alternatives for sub-Saharan African countries, the paper adopts a Two Sample Independent T-Test to empirically analyze the role of agricultural research and development (AR&D) in facilitating a sustainable and inclusive economic growth in the sub-continent. Using two groups of four sub-Saharan African countries as case studies – Group 1 (Togo and Sierra Leone) and Group 2 (Madagascar and Kenya) – the paper’s empirical analysis finds that a methodical investment in agricultural research and development has a strong potential to facilitate economic growth through an increase in the value of agricultural output. KEYWORDS Sub-Saharan Africa, Endemic Poverty, Economic Growth, Fiscal Policy, Monetary Policy, Poverty Rate, Mortality Rate, Agricultural Research and Development (AR&D), Two Sample Independent T-Test, Agricultural Output.